2018
DOI: 10.1055/a-0577-2650
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for advanced duodenal and ampullary adenomatosis in familial adenomatous polyposis: a prospective, single-center study

Abstract: Background and study aims  To determine the clinical features associated with advanced duodenal and ampullary adenomas in familial adenomatous polyposis. Secondarily, we describe the prevalence and clinical significance of jejunal polyposis. Patients and methods  This is a single center, prospective study of 62 patients with familial adenomatous polyposis. Duodenal polyposis was classified according to Spigelman and ampullary adenomas were identified. Patients with Spigelman III and IV duodenal polyposis under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…A prospective study of 62 patients with FAP showed that screening and surveillance with DAE could be useful in FAP patients with advanced duodenal polyposis. However, another study of 18 FAP patients with advanced duodenal polyposis reported that routine DAE is not warranted in patients with FAP because the malignant potential of these lesions is unknown [ 71 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective study of 62 patients with FAP showed that screening and surveillance with DAE could be useful in FAP patients with advanced duodenal polyposis. However, another study of 18 FAP patients with advanced duodenal polyposis reported that routine DAE is not warranted in patients with FAP because the malignant potential of these lesions is unknown [ 71 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, another study of 18 FAP patients with advanced duodenal polyposis reported that routine DAE is not warranted in patients with FAP because the malignant potential of these lesions is unknown. 71,72…”
Section: Statementmentioning
confidence: 99%
“…This study was structured according to the PRISMA 18 recommendations. 18 It was registered in the PROSPERO international database https://www.crd.york.ac.uk/prospero/ 19 with the study number CRD42020202376.…”
Section: Methodsmentioning
confidence: 99%
“…There is little evidence in determining the indication for DAE in familial adenomatous polyposis patients. Screening and surveillance with DAE of SB adenomas could be useful in patients with Spigelman scores III or IV [111], even though the malignant potential of these lesions is unknown [112][113][114].…”
Section: Small Bowel Polyposismentioning
confidence: 99%